Asymmetrical gene flow in five co-distributed syngnathids explained by ocean currents and rafting propensity. Issue 1926 (13th May 2020) - Bertola, Laura D.; Boehm, J. T.; Putman, Nathan F.; Xue, Alexander T.; Robinson, John D.; Harris, Stephen; Baldwin, Carole C.; Overcast, Isaac; Hickerson, Michael J.
Abstract : Ocean circulation driving macro-algal rafting is believed to serve as an important mode of dispersal for many marine organisms, leading to predictions on population-level genetic connectivity and the directionality of effective dispersal. Here, we use genome-wide single nucleotide polymorphism data to investigate whether gene flow directionality in two seahorses ( Hippocampus ) and three pipefishes ( Syngnathus ) follows the predominant ocean circulation patterns in the Gulf of Mexico and northwestern Atlantic. In addition, we explore whether gene flow magnitudes are predicted by traits related to active dispersal ability and habitat preference. We inferred demographic histories of these co-distributed syngnathid species, and coalescent model-based estimates indicate that gene flow directionality is in agreement with ocean circulation data that predicts eastward and northward macro-algal transport. However, the magnitude to which ocean currents influence this pattern appears strongly dependent on the species-specific traits related to rafting propensity and habitat preferences. Higher levels of gene flow and stronger directionality are observed in Hippocampus erectus, Syngnathus floridae and Syngnathus louisianae, which closely associated with the pelagic macro-algae Sargassum spp., compared to Hippocampus zosterae and the Syngnathus scovelli / Syngnathus fuscus sister-species pair, which prefer near shore habitats and are weakly associated with pelagic Sargassum . This study highlights how the combination of population genomic inference together with ocean circulation data can help explain patterns of population structure and diversity in marine ecosystems.